Răspuns :
4×(3+2+4)=
4×(5+4)
4×9
36
Al doilea mod
4×(3+2+4)=
(4×3)+(4×2)+(4×4)
12+8+16
20+16
36
A doua ecuatie
5×(9-3-5)=
5×(6-5)
5×1
5
Al doilea mod
5×(9-3-5)
(5×9)-(5×3)-(5×5)
45-15-25
30-25
5
Sper ca te-am ajutat!BAFTA!!
4×(5+4)
4×9
36
Al doilea mod
4×(3+2+4)=
(4×3)+(4×2)+(4×4)
12+8+16
20+16
36
A doua ecuatie
5×(9-3-5)=
5×(6-5)
5×1
5
Al doilea mod
5×(9-3-5)
(5×9)-(5×3)-(5×5)
45-15-25
30-25
5
Sper ca te-am ajutat!BAFTA!!
1. Folosind paranteza;
2.Folosind distributivitatea inmultirii fata de adunare si scadere
4×(3+2+4)=4×9=36
4×(3+2+4)=4×3+4×2+4×4=12+8+16=36
5×(9-3-5)=5×1=5
5×9-5×3-5×4=45-15-25=5
2.Folosind distributivitatea inmultirii fata de adunare si scadere
4×(3+2+4)=4×9=36
4×(3+2+4)=4×3+4×2+4×4=12+8+16=36
5×(9-3-5)=5×1=5
5×9-5×3-5×4=45-15-25=5